Determinants of competitiveness among smallholder avacado farmers in Vhembe District of Limpopo Province, South Africa - Masikhwa, Humbulani (My University, 2018)
The avocado industry is a major industry in South Africa and this can be seen by its economic contribution. Limpopo Province is one of the major avocado producing areas in South Africa, and avocado production within the province ranges from smallholder to commercial production. Smallholder avocado producers within the province have a significant role to play, especially if their full potential is unleashed. For smallholder farmers to play such a role they need to be competitive. The concept of competitiveness can be defined as the ability of an industry or firm to compete successfully in order to achieve sustainable growth while earning at least the opportunity cost on resources employed. The main aim of this study was to analyse the determinants of competitiveness of smallholder avocado farmers in the Vhembe District of the Limpopo Province based on the Porter’s Diamond model framework in order to assess the level of competitiveness of farmers and to establish how the farmers can be assisted to reach their full potential. The study was conducted in the Vhembe District Municipality and a sample of 60 farmers was interviewed. SPSS (SPSS 26.0) was used to analyse the data. Three analytical techniques were used in the analysis for this study. Firstly, factor analysis was used to reduce and group the number of variables associated with competitiveness of the farmers. Secondly, profitability analysis through enterprise budgeting was used to categorise the farmers into two groups; competitive and noncompetitive. Thirdly, Logistic regression was used to establish the socio-economic and Porter’s Diamond model determinants that could be linked to the competitiveness of the farmers. From the factor analysis, 5 factors were extracted, namely; “chance”, “government, related and supporting industries”, “factor conditions”, “firm strategy structure and rivalry” and “demand conditions”. From the profitability analysis the farmers were grouped into competitive and non-competitive categories with 22 farmers classified as being competitive and 38 farmers as being non-competitive. From the results of logistic regression, 7 out of 12 hypothesised variables were found to be statistically significant, these were; age of farmer, number of trees planted, related and supporting industries, firm strategy structure and rivalry, chance, demand conditions and factor conditions. Chance was the only variable with a statistically significant v negative influence on the competitiveness of the farmers, this was because factors that were tested for their influence on the competitiveness of the farmers are among others: Crime, HIV/AIDS, fires, frost and floods. Based on the research findings, several policy suggestions were made, these include; mentorship and encouragement of youth participation in farming, provision of agricultural land, capacity building for farmers, government support and stakeholder mobilization, specialized extension service and formation of cooperatives as well as encouraging commercialization.
Thesis (MSc. (Agricultural Economics)) -- University of Limpopo, 2018
Keywords: Avocado industry; Competitiveness; Commercial production; Smallholder production; Smallholder farmers; Avocado -- South Africa -- Limpopo; Avocado industry; Farmers -- Economic conditions